One-dimensional hard rod fluid in a disordered porous medium: scaled particle theor - Holovko, M.; Patsahan, T.; Dong, W. (Condensed Matter Physics, 2012)
The scaled particle theory is applied to a description of thermodynamic properties of one-dimensional hard rod fluid in disordered porous media. To this end, we extended the SPT2 approach, which had been developed previously. Analytical expressions are obtained for the chemical potential and pressure of a hard-rod fluid in hard rod and overlapping hard rod matrices. A series of new approximations for SPT2 are proposed. It is shown that apart from two well known porosities such as geometrical porosity and specific probe particle porosity, a new type of porosity defined by the maximum value of packing fraction of fluid particles in porous medium should be taken into account. The grand canonical Monte-Carlo simulations are performed to verify the accuracy of the SPT2 approach in combination with the new approximations. It is observed that the theoretical description proposed in this study essentially improves the results up to the highest values of fluid densities. Застосовано теорiю масштабної частинки до опису термодинамiчних властивостей плину в матрицi в рамках моделi твердих стержнiв. З цiєю метою розвинуто теоретичний пiдхiд, вiдомий як SPT2. Отримано аналiтичнi вирази для хiмiчного потенцiалу i тиску плину в матрицi двох типiв: твердi стержнi та твердi стержнi, що перекриваються. Запропоновано низку нових наближень в рамках SPT2. Показано, що, крiм вiдомих геометричної пористостi та пористостi пробної частинки, важливим є ще iнший тип пористостi, який визначається максимально можливою упаковкою плину, доступною в пористому середовищi. Щоб перевiрити теорiю SPT2 та оцiнити точнiсть запропонованих наближень, проведено комп’ютерне моделювання методом Монте-Карло у великому канонiчному ансамблi. Зауважено, що теоретичний опис, представлений у даному дослiдженнi, суттєво покращує результати аж до найвищих густин плину.